An association between infantile haemangiomas and erythropoietin treatment in preterm infants. Issue 1 (5th May 2011) - Doege, Corinna; Pritsch, Maria; Frühwald, Michael C; Bauer, Jacqueline
Abstract : Background: Infantile haemangiomas are benign vascular neoplasms that occur frequently in premature infants. The authors hypothesised that in addition to gestational age and birth weight, erythropoietin therapy may influence the incidence of these soft tissue tumours in preterm infants. Methods: 2563 infants born prematurely and admitted to the Division of Neonatology, University of Heidelberg Medical School were investigated in a retrospective analysis. Hospital charts for all infants were reviewed for clinical data. The primary endpoint was the percentage of infants who had received erythropoietin treatment and were diagnosed with a haemangioma. Results: Haemangiomas were diagnosed in 4.3% (n=110) of the 2563 preterm infants. These 110 infants had a median gestational age of 29 weeks (IQR 27–33 weeks) and the female:male ratio was 1.8:1. A higher incidence of haemangiomas (12–15%) was detected in premature infants with a lower gestational age (<31 weeks). Erythropoietin therapy was shown to be an independent risk factor after adjusting for all other known factors and oxygen therapy in multivariable analysis (HR 2.82, 95% CI 1.55 to 5.12). Subgroup analysis revealed that the effect was more pronounced in male than female infants (HR 3.61, 95% CI 1.52 to 8.57). Conclusions: This retrospective study demonstrates that erythropoietin treatment is associated with an increase in the incidence of these benign vascular tumours after adjusting for all other factors.